Encounter Groups Experience - Self Esteem and Subjective Wellbeing. - Pires, Mónica (2009)
SELF-ESTEEM It implies two actions on the person itself: measuring and valuing his way of being. Tap (2006) • Plays a fundamental part on the variables that alow the person to affirm his identity, to develop stress coping strategies, social integration competences and to elaborate a meaningfull existential project. •Depends on the way the person mobilize different strategies and efforts with the goal of obtaining a good personal, professional and social integration